Consistency of Planning and Budgeting of Basic infrastructure in West Java Province - Bayu Kharisma; Kodrat Wibowo (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
Planning and budgeting play an essential role in achieving development goals in the national and regional scale, especially fundamental development such as infrastructure. Development planning documents through the Medium-Term Expenditure Framework (MTEF) approach presents the relationship between policy priorities and available budgets. The development planning document is implemented annually through the Regional Development Budget (APBD) through a Public Expenditure Management (PEM) approach. Consistency between the two documents is needed to achieve development goals. The purpose of this study is to analyze the consistency between the MTEF and PEM in the Regional Medium Term Development Plan (RPJMD) and the realization of the APBD on basic infrastructure in West Java Province during the period 2016-2017. The research used a method of comparing programs and budgets according to the number, variance, and percentage of changes between MTEF and public budget management and Analytic Hierarchy Process (AHP). The results showed that the MTEF and PEM in infrastructure in West Java were not consistent. The difference was caused by the difference in agreement; where MTEF is an agreement between the executive only and PEM is approved by the executive and legislative. Keywords: Consistency, MTEF, PEM, planning and budgeting, infrastructure, AHP.